Characterization of endophytic bacteriome diversity and associated beneficial bacteria inhabiting a macrophyte Eichhornia crassipes - Fan, Di; Schwinghamer, Timothy; Liu, Shuaitong; Xia, Ouyuan; Ge, Chunmei; Chen, Qun; Smith, Donald L. (Frontiers in Plant Science, 2023)
The endosphere of a plant is an interface containing a thriving community of endobacteria that affect plant growth and potential for bioremediation. Eichhornia crassipes is an aquatic macrophyte, adapted to estuarine and freshwater ecosystems, which harbors a diverse bacterial community. Despite this, we currently lack a predictive understanding of how E. crassipes taxonomically structure the endobacterial community assemblies across distinct habitats (root, stem, and leaf). In the present study, we assessed the endophytic bacteriome from different compartments using 16S rRNA gene amplicon sequencing techniques and verified the in vitro plant beneficial potential of isolated bacterial endophytes of E. crassipes. Our results indicate that plant compartments displayed a significant impact on the endobacterial community structures. Stem and leaf tissues were more selective, and the community exhibited a lower richness and diversity than root tissue. The taxonomic analysis of OTUs showed that the major phyla belonged to Proteobacteria and Actinobacteriota (> 80% in total). The most abundant genera in the sampled endosphere recorded were Delftia in stem and leaf samples. Members of the family Rhizobiaceae, such as Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium, were mainly associated with leaf tissue, whereas the genera Nannocystis and Nitrospira from the families Nannocystaceae and Nitrospiraceae, respectively, were significantly associated with root tissue. Piscinibacter and Steroidobacter were putative keystone taxa of stem. Most of the endophytic bacteria isolated from E. crassipes showed in vitro plant beneficial effects known to stimulate plant growth and induce plant resistance to stresses. This study provides new insights into the distribution and interaction of endobacteria across different compartments of E. crassipes. Future study of endobacterial communities, using both culture-dependent and -independent techniques, will explore the mechanisms underlying the wide-spread adaptability of E. crassipes to various ecosystems and contribute to the development of efficient bacterial consortia for bioremediation and plant growth promotion.